Evaluation of the Safety of High-Salt Wastewater Treatment in Coal Chemical Industry Based on the AHP Fuzzy Method - Shijun Guo; Shubham Sharma; Alibek Issakhov; Nima Khalilpoor (Journal of Chemistry)
Aim. Epichlorohydrin (ECH) is a widely used chemical product. The production of glycerol has its irreplaceable advantages. With the development of biodiesel industry, it will become the main trend of ECH production in the future. Methods. A vacuum evaporation device is built to investigate the effect of evaporation on the treatment of this kind of high-salt wastewater, and the feasibility of the thermodynamic equation of the simulation process is verified. Process. An AHR fuzzy mathematics evaluation algorithm is used to compare experimental values with simulated numerical values in brine. Results and Conclusions. In the multieffect evaporation process simulation with glycerin-containing brine, the amount of salt precipitated by unit steam energy is arranged in order from more to less than that of seven-effect parallel flow evaporation, is greater than five-effect parallel flow evaporation, and is larger than three-effect parallel flow evaporation, which shows that the increase of validity number is beneficial to the utilization of heat.